Tildrakizumab for the treatment of moderate-to-severe psoriasis: a 52-week, real-world Portuguese multicentric study - Tiago Torres; Paulo Varela; Pedro Mendes Bastos; Sofia Magina; Martinha Henrique; Paulo Ferreira (BioExcel Publishing Ltd, 2024)
Background: Real-world evidence plays a pivotal role in validating the efficacy of biologic drugs beyond the controlled environment of randomized trials. This study aimed to evaluate the effectiveness of tildrakizumab in treating moderate-to-severe psoriasis within a real-world setting over a 52-week period in Portugal. Methods: This multicentric, prospective, observational study included adult patients with moderate-to-severe psoriasis. All participants received tildrakizumab 100 mg at weeks 0 and 4, followed by a maintenance dose every 12 weeks, and were monitored for 52 weeks. Primary endpoints were determined based on Psoriasis Area and Severity Index (PASI) assessments at baseline, 16 (±2) weeks, 28 (±2) weeks and 52 (±2) weeks. Results: A total of 54 patients were enrolled in the study (56% men, mean age of 50.3 ± 14.4 years). Half of the sample (n=27) had no prior experience with biologic treatments. About 74% of patients (n=40) presented at least one comorbidity during the study, with psoriatic arthritis being the most prevalent (29.6%). By week 52, there was a significant decrease in the mean PASI from 17.8±10.3 at baseline to 1.3±1.9 (p<0.001), indicating an overall improvement of 93%. By week 52, more than 85% of patients attained PASI ≤5, more than 80% reached PASI ≤3, and nearly 60% achieved PASI ≤1. Infections were observed in 9.3% of patients, and one patient required hospitalization (1.9%). The cumulative proportion of patients continuing treatment at 52 weeks was 88.9%. Conclusions: This study demonstrates that tildrakizumab is an effective and safe agent for the treatment of moderateto- severe psoriasis in a diverse, real-world setting.